Acute exposure to copper oxide nanoparticles impairs testicular function and sperm quality in adult male albino rats - Lamiaa Hassan; Ibrahem M. A. Hasan; Zeinab Al-Amgad; Hassan Ahmed (SVU-International Journal of Veterinary Sciences, 2024)
Copper oxide nanoparticles (CuO NPs) are metallic nanoparticles fulfilling several functions such as good conductivity, catalyst, used in sensors and energy storage devices, and antibacterial characteristics. However, the cytotoxicity and particular mechanisms of exposure to CuO NPs on male testicular function are still elusive. In the current study, seventy-five mature male albino rats received single doses of 0, 100, 200, 1000, and 2000 mg/kg CuO NPs by oral gavage. Blood and epididymal semen as well as testicular tissue were collected 2, 8, and 15 days after administration. Serum testosterone level, sperm motility, count, morphology, viability, and gonadosomatic index (GSI) were assessed at the same time; histological structure of the testes was examined. The result revealed that CuO NPs significantly reduced serum testosterone levels, suppressed sperm concentration, and significantly elevated abnormal and dead sperm percent. Furthermore, testicular tissue showed degeneration of germ, Sertoli, Leydig cells, and spermatocytes with the incidence of vacuolation and inflammatory cell infiltration. In conclusion, CuO NPs exert adverse and irreversible effects on testicular function and sperm physiological characteristics; these harmful effects were markedly observed after administration of high doses of CuO NPs.